One‐Pot Sequential Kumada–Tamao–Corriu Couplings of (Hetero)Aryl Polyhalides in the Presence of Grignard‐Sensitive Functional Groups Using Pd‐PEPPSI‐IPentCl1. Issue 26 (11th April 2019) - Sinha, Narayan; Champagne, Pier Alexandre; Rodriguez, Michael J.; Lu, Yu; Kopach, Michael E.; Mitchell, David; Organ, Michael G.
Abstract: We report a general and rapid chemoselective Kumada–Tamao–Corriu (KTC) cross‐coupling of aryl bromides in the presence of chlorides or triflates with functionalized Grignard reagents at 0 °C in 15 min by using Pd‐PEPPSI‐IPent Cl (C4 ). Nucleophiles and electrophiles (or both) can contain Grignard‐sensitive functional groups (‐CN, ‐COOR, etc.). Control experiments together with DFT calculations suggest that transmetallation is rate limiting for the selective cross‐coupling of Br in the presence of Cl/OTf with functionalized Grignard reagents. One‐pot sequential KTC/KTC cross‐couplings with bromo–chloro arenes have been demonstrated for the first time. We also report the one‐pot sequential KTC/Negishi cross‐couplings usingC4 showcasing the versatility of this methodology. Abstract : All‐in‐One ! A general and efficient chemoselective Kumada–Tamao–Corriu (KTC) coupling of an aryl bromide in the presence of a chloride or triflate with functionalized Grignard reagents using Pd‐PEPPSI‐IPent Cl has been described to prepare functionalized biaryl chlorides or triflates. We also demonstrated a one‐pot sequential KTC/KTC and KTC/Negishi couplings using a single set of conditions (see scheme).